PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MENGGUNAKAN MODEL PROBLEM BASED LEARNING MATA PELAJARAN PENDIDIKAN PANCASILA KELAS II DI SDN 02 TIMPEH - M. Anggrayni; Agus Saputra; Diana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is based on problems in Pancasila education learning, namely that in the ongoing learning process activities, students have difficulty understanding the material and learning outcomes are still low. The teaching materials used are less interesting and the learning atmosphere seems monotonous. This certainly affects student learning outcomes. The aim of this research is to develop "Development of Student Worksheets (LKPD) using the Problem Based Learning model for class II Pancasila Education subjects at SDN 02 Timpeh", in order to add to existing teaching materials at the school and to produce "Development of Student Worksheets ( LKPD) uses the Problem Based Learning model for class II Pancasila Education subjects at SDN 02 Timpeh” which is valid, practical and effective. So that it can improve student learning outcomes at SDN 02 Timpeh.This research is R & D (Research and Development) research using the ADDIE research model. The development model used is the ADDIE model. The ADDIE model consists of five stages, namely, analysis, design, development, implementation and evaluation. Based on the results of research on the validation of the Pancasila Education LKPD which was carried out by six validators, namely, graphic validator, material validator, language validator, question validator and teaching module validator. An average score of 89.4% was obtained in the very valid category. As well as the results of practicality carried out by practitioners, namely class II.B teachers, who obtained a score of 98.2% in the very valid category, and for the students themselves the average score 86,57% was obtained in the category very practical. Meanwhile, the results of this effectiveness test are in the form of a distribution of test questions completed by students with an average completion score of 87.5% in the very effective category. So that the LKPD that has been created can be said to be effective and can be used in the learning process at SDN 02 Timpeh.